PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH PRODUK BEASISWA PADA ASURANSI JIWA BERSAMA BUMIPUTERA 1912 CABANG KENDARI - Gunawan Gunawan; Muhammad Fachmi (Jurnal Bisnis dan Kewirausahaan, 2016)
The purpose of this research was to examine the effect of service quality to customer satisfaction AJB Bumiputera 1912 branch Kendari. Sampled units in this research are costumers of AJB Bumiputera 1912 Kendari Branch who have received scholarships in the period February 1st, 2013 until July 31st, 2013. Number of respondents 85 costumers, who were taken by systematic sampling methods. Data analysis is using Partial Least Square (PLS) with SmartPLS program. The results showed that; the better of Service Quality can improve costumer satisfaction of AJB Bumiputera 1912, Branch of Kendari. This means that, costumer satisfaction can have better impact when AJB Bumiputera 1912, Branch of Kendari can improve the service quality as a result better implementation. The Service Quality formed by five dimension is tangible, reliability, responsiveness, assurance, and empathy, it appears that the dimension of the most powerful influence to service quality is tangible dimensions. This is showed that should be AJB Bumiputera 1912, Branch of Kendari maximize the tangible dimensions to improve service quality because will be influence to costumer satisfaction. Besides that, the majority of respondents were male customers showed that male customers who act as heads of households tend to shift risk to the insurance, so that in case of risk to the household head, then the continuation of children's education expenses can be assured.